2013
DOI: 10.3329/bjpt.v20i1.15459
|View full text |Cite
|
Sign up to set email alerts
|

Nutlet morphology and its taxonomic significance in the genus Mentha L. (Lamiaceae) from Turkey

Abstract: The nutlet morphology of 11 taxa of Mentha L. (M. pulegium, M. aquatica (SEM). The shape of all studied nutlets was broadly oblong or ovoid. Nutlet size ranged from 0.54 to 0.97 mm in length and from 0.37 to 0.66 mm in width. The smallest and biggest nutlets were found in M. × villoso-nervata and M. aquatica, respectively. The Mentha taxa studied can be divided into three groups, based on nut sculpturing type such as distinctly bireticulate, inconspicuously bireticulate and reticulate. This study has shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In Stachys (Salmaki et al, 2008) nutlet micromorphology provided valuable data in separating the related species within sections, although these characters were not useful in separating large natural groups. Variations in size and the type of sculpturing as well as the shape of its composing cells had been considered to provide the most valuable characters at species level (e.g., Kahraman et al, 2011;Tarimcilar et al, 2013;Salmaki et al, 2008;Eyvazadeh Khosroshahi & Salmaki, 2018). For instance, the polygonal cells in M. peregrinum L. (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In Stachys (Salmaki et al, 2008) nutlet micromorphology provided valuable data in separating the related species within sections, although these characters were not useful in separating large natural groups. Variations in size and the type of sculpturing as well as the shape of its composing cells had been considered to provide the most valuable characters at species level (e.g., Kahraman et al, 2011;Tarimcilar et al, 2013;Salmaki et al, 2008;Eyvazadeh Khosroshahi & Salmaki, 2018). For instance, the polygonal cells in M. peregrinum L. (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The variation in color, size and ornamentation of mericarp helped to identify species. Tarimcilar et al (2013) investigated nutlet morphology of 11 taxa of Mentha distributed throughout Turkey using SEM. In their study, they divided Mentha into three groups, based on nutlet sculpturing type such as distinctly bireticulate, inconspicuously bireticulate and reticulate.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many studies on the nutlet characters of family Lamiaceae as shown above, only few Egyptian species have been treated e.g. Teucrium polium ( Marin et al 1994); Salvia sclarea ( Marin et al 1996 andMousavi et al 2013); Salvia palaestina ( Kahraman and Dogan 2010) and Mentha longifolia ( Tarimcilar et al 2013). Therefore the present investigations deal with morphological characters of nutlet (mericarp) of 28 taxa belonging to 15 genera of Lamiaceae in Egypt, especially in Sinai, to find good nutlet characters for comparison and delimitation of genera and species in the family.…”
Section: Introductionmentioning
confidence: 99%
“…Moon et al (2009) showed the importance of nutlet micromorphology in character Evolution of the Tribe Mentheae (Nepetoideae, Lamiaceae).This type of research was carried out on allied genera such as Salvia L. in Turkey [15] and in NE Iran [7]. Nepeta L. in Turkey [10] and in Kashmir Himalaya [19] and Mentha L. in Turkey [18]. Based on the results of above-mentioned studies, the networking pattern or cell shape of nutlet surface is one of the useful characteristics in identification at the generic and specific level of Lamiaceae [19,10,1,18].…”
Section: Introductionmentioning
confidence: 99%
“…Nepeta L. in Turkey [10] and in Kashmir Himalaya [19] and Mentha L. in Turkey [18]. Based on the results of above-mentioned studies, the networking pattern or cell shape of nutlet surface is one of the useful characteristics in identification at the generic and specific level of Lamiaceae [19,10,1,18]. The aim of the present research is to focus on the shape and ornamentation of nutlet of Thymus species distributed in NE Iran.…”
Section: Introductionmentioning
confidence: 99%